Effect of Plyometric Training on agility and vertical Jump U- 15 Male Handball Project in kembata tambaro Zone - Dolebo Awano, Tesfaye (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
The purpose of the study was to examine the effects of plyometric exercise in improving explosive power, speed, flexibility and agility performance .To achieve the purpose of the study 25 male handball project were selected as target group and their age was U-15 years. They were assigned in two groups Experimental and control group and the selected exercises were given for 12 weeks. The variables which were selected for this study 35m sprint, pro-agility (T-’test), V sit and reach test, and vertical jump were measured. Pre and post tests were conducted for all 25 male study target group and the test results were recorded. The collected data were analyzed by paired sample t-test and independent t-test using SPSS version twenty one (V.21). Descriptive statistics concerns the development of certain measures from the raw data. Under the descriptive statistics, the study encompasses that the Mean, Standard deviation, percentages, and Correlation was used for this study. Charts/graphs were employed to illustrate and elaborate on the results of records. Pearson product-moment correlation was also employed to associate the relationship between the plyometric exercise effects on player’s physical fitness. Plyometric training program have shown significant improvement on agility, power and flexibility performance of Kembata tambaro zone handball project players.